2009
DOI: 10.1152/ajpregu.90866.2008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of acute and chronic caloric restriction and metabolic glucoprivation on spontaneous physical activity in obesity-prone and obesity-resistant rats

Abstract: Teske JA, Kotz CM. Effect of acute and chronic caloric restriction and metabolic glucoprivation on spontaneous physical activity in obesity-prone and obesity-resistant rats. Am J Physiol Regul Integr Comp Physiol 297: R176 -R184, 2009. First published May 6, 2009 doi:10.1152/ajpregu.90866.2008 and metabolic glucoprivation affect spontaneous physical activity (SPA), but it's unknown whether these treatments similarly affect SPA in selectively bred obesity-prone (OP) and -resistant (OR) rats. OR rats have grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…Depending on the animal species examined, both decreases and increases in locomotor activity have been described in response to limited food supplies (Pirke et al, 1993;Weed et al, 1997;Geng et al, 2007;Teske and Kotz, 2009;Boehm et al, 2010;Gingerich et al, 2010;Yu et al, 2010). However, gait-specific effects have not been considered.…”
Section: Received 1 November 2013; Accepted 10 April 2014mentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the animal species examined, both decreases and increases in locomotor activity have been described in response to limited food supplies (Pirke et al, 1993;Weed et al, 1997;Geng et al, 2007;Teske and Kotz, 2009;Boehm et al, 2010;Gingerich et al, 2010;Yu et al, 2010). However, gait-specific effects have not been considered.…”
Section: Received 1 November 2013; Accepted 10 April 2014mentioning
confidence: 99%
“…In contrast, rats show hyperactive wheel running in response to starvation (Koubi et al, 1991;Pirke et al, 1993). Similarly, caloric restriction increases physical activity in rats (Geng et al, 2007;Teske and Kotz, 2009) and rhesus monkeys (Weed et al, 1997). It is of note that up to 80% of human patients with the eating disorder anorexia nervosa show excessive physical activity (Koubi et al, 1991;Hebebrand et al, 2003).…”
Section: Research Articlementioning
confidence: 99%
“…To avoid potential effects of recent food intake on gene expression, food was removed from the cages between 0700 and 0800. At this time, food intake is at a minimum in rodents and is similar between OR and Sprague-Dawley rats (48). Animals were euthansized between 1100 and 1200.…”
Section: Specific Experimental Designsmentioning
confidence: 99%
“…We used a selectively bred rodent model of obesity resistance, the OR rats, whereby phenotypic traits are expressed on a low-fat diet (39). We compared OR rats to Sprague-Dawley rats instead of the selectively bred obesity-prone rats, as we have found that Sprague-Dawley and obesity-prone rats are similar behaviorally and phenotypically and respond to orexin similarly (48,49). We hypothesized that 1) analysis of orexin receptors from multiple brain sites would differentiate OR and Sprague-Dawley rats and identify orexin receptors in the LC as significant to the OR phenotype; 2) compared with Sprague-Dawley rats, OR rats would have greater SPA, energy expenditure, SPA following orexin A infusion into the LC, and lower adiposity; and 3) orexin A-induced hyperphagia would be similar between groups.…”
mentioning
confidence: 99%
“…In Wistar rats, whereas moderate (30%) feed restriction did not change SPA, severe (approximately 80%) restriction reduced spontaneous activity, resulting in energetic economy 32 . In another study, chronic caloric restriction (CR) increased SPA during the time interval preceding anticipation of food in obesity-prone and Sprague-Dawley rats, but not in obesity-resistant rats, which already have elevated basal SPA 33 . Brzek et al 25 investigated the effect of a moderate CR on SPA in mice divergently selected for high or low basal metabolic rate.…”
Section: Running Title: Spa and Energy Homeostasis Calorie Restrictionmentioning
confidence: 99%